Insect protein: a pathway to sustainable protein supply chains, challenges, and prospects - Mohamad, Azizah; Tan, Chun Keat; Abdul Karim Shah, Nor Nadiah; Nayan, Nazri; Ibrahim, Ahmad; Abdi, Gholamreza; Muhammad Aadil, Rana (Elsevier, 2025)
Insect protein holds promise in the global search for a sustainable protein supply chain, offering potential solutions to the challenges of conventional protein sources. This review explores the three pillars of sustainability – economic, environmental, and social – in the context of insect protein. Economically, insect protein is valued for its feed conversion and nutritional benefits in animal diets, offering a cost-effective alternative to conventional protein sources. Environmentally, insect farming presents a lower carbon footprint and reduced land and water usage compared to livestock production. However, concerns over the presence of heavy metals and bioaccumulates in the insect protein highlight the need for careful monitoring and safety standards. Socially, the widespread adoption of insect protein depends on overcoming regulatory hurdles and ensuring robust legislation to guarantee product safety, quality, and consumer acceptance. The review addresses critical barriers such as scaling production, developing efficient protein extraction technologies, and navigating complex regulatory framework. Insect protein shows strong potential to enhance global food security and promoting environmental sustainability, yet overcoming these challenges will require continued research, technological innovation, and cross-sector collaboration. By addressing these gaps, insect protein can play a crucial role in building more sustainable protein supply chain for both food and feed production.